Analisa Perambatan Gelombang Surja Berjalan pada Belitan Trafo Distribusi - Hery Purnomo; Mahfudz Shidiq (Fakultas Teknik, Universitas Brawijaya, 2010)
These instructions give you guidelines for preparing papers for EECCIS Journal. This document based on IEEE Transaction and Journal.. Use this document as a template if you are using Microsoft Word 6.0 or later. Otherwise, use this document as an instruction set. The electronic file of your paper will be formatted further at EECCIS. Define all symbols used in the abstract. Do not cite references in the abstract. Do not delete the blank line immediately above the abstract; it sets the footnote at the bottom of this column.Index Terms—About four key words or phrases in alphabetical order, separated by commas.